Carlos Alberto Torres em entrevista: da Educação Comparada aos planos futuros de um “intelectual do mundo” - Lopes, Rodrigo de Macedo; Silva, Camila Ferreira da; Alves, Mariana Gaio (Educação, 2018)
---